Comfort and infection control of chitosan-impregnated cotton gauze as wound dressing - Souza, Jefferson M. (2019)
The aim of this study was to evaluate the thermo-physiological comfort properties of surgical cotton gauze coated with chitosan (CH) and its effectiveness for the prevention of bacterial colonization. Gauze was coated with CH at mass fractions of 0.50, 0.25, 0.125, 0.10, 0.063 wt% and the friction, flexibility, thermal, moisture management and mechanical properties were evaluated. The best performing gauze in terms of comfort (0.125 wt%) was further evaluated for its ability to inhibit the growth of microorganisms such as bacteria and yeast. Results indicate that the functionalized medical gauze could induce low friction on the wound bed allowing a good degree of moisture and high absorption capacity of wound exudates. Moreover, it shows antimicrobial properties against medical-relevant pathogens. This biofunctional medical gauze demonstrates to deliver an efficient antimicrobial coating and promote the best conditions for maintenance of the wound microenvironment.